Arbetsrelaterad stress : En studie om hur stress påverkar arbetssituationen för sjuksköterskor - Lindgren, Sarah; Andersson, Sofia (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
The aim of this study is to investigate how stress affects nurses in Luleå Kommun. The questions regarding this issue are;” Does stress affect the quality of the task?” and” How does stress affect the motivation nurses feel at work”. Qualitative data methods have been used. This is evident through the ten semi-structured interviews given to participating nurses employed within Luleå kommun. These interviews were subsequently processed through a thematic method of analysis. This approach is abductive, as the information has been collected and construed via empirical data and theory. The results show that the respondents felt their departments were short-handed. As a result, their work settings were perceived as stressful. Due to this high-stress environment, the respondents also felt that the support from their colleagues was of greater importance than the support from their management team. Due to the lack of staff, the contact between the management team and the employees was scarce. Further analysis of the results found that everyone serving in the hospital had the same basic idea and willingness to help individuals to a healthy life. Conclusively, if the same determination is shown, particularly from management team, to assist in a healthy working climate, through an increase in staff and more direct support given to employees, stress will most certainly be reduced in employees. Syftet med studien är att undersöka hur stress påverkar sjuksköterskor i Luleå kommun. Frågeställningarna lyder därmed följande: ”på vilket sätt påverkar stress utförandet av arbetsuppgifterna?” och ”På vilket sättpåverkar stress sjuksköterskans arbetsmotivation?”. Metoden var av kvalitativ karaktär då den består av tio semistrukturerade intervjuer med sjuksköterskor som är verksamma inom Luleå kommun. Resultatet visar att respondenterna upplever en stor underbemanning på avdelningarna. Som följd upplevs deras arbetssituation som stressfull. På grund av rådande situation upplever även respondenterna att stödet från kollegorna är av ...